Development of Website-Based Learning Media Integrated Inquiri Learning Strategies in Learning Thermochemical Matter Chemistry - Bambang Enra Priando Purba; Ida Duma Riris; Zainuddin Muchtar (BIRCU, 2021)
This research is a research on the development of Website learning media. This study aims to produce a product in the form of website learning media on thermochemical material that has been developed and its effect on student learning outcomes. This research was conducted by analyzing several Thermochemical learning websites with good ratings by 15 teachers who teach Chemistry in Serdang Bedagai Regency. From this analysis, it was obtained that the average count for Website A was 3.64 and Website B was 3.83, with sufficiently valid information but still requiring improvement in its presentation. The results of the analysis become a reference point in developing the Website learning media. The website that has been developed is analyzed according to the BSNP standard by 2 IT learning experts with an average result of 4.76 with very valid criteria. In addition, 15 teachers obtained an average score of 4.74 with very valid criteria. Limited trials of student learning outcomes were analyzed using independent t-test, with a value of t-count> t-table (3.89> 1.70), which means that with the implementation of integrated website media the inquiry learning strategy is higher than the KKM of the school at the level of significance of 0.05.